The Battle Of Actors' Roles In Criminal Justice (Case Study: Murder of Brigadier Yosua Hutabarat) - Siahaan, Chontina; Panggabean, Mompang; Litha, Trianna Sampe; Pesiwarissa, Louis Carilo Daniel (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The murder of Brigadier Nofriansyah Yosua Hutabarat, considered by the community to be very barbaric, sadistic and inhumane was carried out by his own superior, FS who served as the Head of the Police Propam Division on Jl. Duren Tiga, South Jakarta. This murder incident is a very viral news from August 11, 2022 to February 13, 2023 because it is full of scenarios and lies during the criminal justice process taking place in the district court. The purpose of this research is to uncover and explore how the role of actors involved in the criminal justice process both directly in court and outside the court such as the public who attend the trial and give opinions through social media. The stages of this research method begin by collecting viral news that describes the role of each actor. The theories used in researching this case are the semiotic theory of Roland Barthes, the dramaturgy theory of Erving Goffman and the progressive legal theory of Satjipto Rahardjo. This research method is qualitative descriptive with a constructivist paradigm. The research approach is Case Study.The result of this study is that the actors fight according to the categorization in the criminal justice process, namely the perpetrators, participate in doing, moving, helping to do. Netizens are actors outside the court who play a role in overseeing the trial by conveying public opinion through the media. The output of this research, in addition to the Sinta 2 journal, also makes a model of the role of actors in criminal justice. The recommendation of this study is that legal opinion is not always the basis for judges' consideration, but in the era of information technology, public opinion is a necessity to be considered.